Interdisciplinary approach for qualitatively monitoring coastline dynamics in North Java Coast, Case study: Karawang Regency Indonesia. Issue 1 (December 2021) - Novico, F; Siddik, D A; Lufiandi,; Albab, A; Mulia, A; Kusnida, D; Komarudin, R A; Ranawijaya, D; Kamariah, I; Endyana, C; Bachtiar, H; Hendarmawan,
Abstract: The coast of north Java is the most rapid development area among other parts of Indonesia. Since the North Java Coast is dominated by mild slope, soft-loose quaternary sediment and provoked by the sea thus the vulnerability of it is the most challenging issue to be assessed. Karawang is the representative area to investigate the scientific reason of coastal dynamics. This study aims to reveal the coastline changing based on RBI (1210-211, 1210-212, 1210-221, 1210-542, 1210-543, 1210-544 and 1210-631) and LPI (1210-04 and 1209-01) maps, hydrodynamics simulation and field measurements associated with abrasion and accretion. The equalizing procedure has been applied for a benchmark of zero coastlines that LPI and RBI data were used to observe the back and forth of coastline changing throughout 2000 and 2018. The results show five districts, Tirtajaya, Pakisjaya, Cilebar, Cibuaya and Pedes have the highest abrasion with an average magnitude of 11.3 m/year, 9.1 m/year, 6.9 m/year, 5.1 m/year and 3.7 m/year respectively within a total 489 ha disappear area. By all integrated analysis data so we can conclude that the dominated monsoonal longshore current is east to west and working on the dominantly terrigenous coastal alluvium and intercalated by carbonatic marine sediment.